1989
DOI: 10.1128/mcb.9.12.5508
|View full text |Cite
|
Sign up to set email alerts
|

Complex regulation of transforming growth factor beta 1, beta 2, and beta 3 mRNA expression in mouse fibroblasts and keratinocytes by transforming growth factors beta 1 and beta 2.

Abstract: Regulation of transforming growth factor Il1 (TGFII1), TGF(2, and TGF0i3 mRNAs in murine fibroblasts and keratinocytes by TGFIII and TGFI2 was studied. In quiescent AKR-2B fibroblasts, in which TGFOi induces delayed stimulation of DNA synthesis, TGFII1 autoregulation of TGFI1 expression was observed as early as 1 h, with maximal induction (25-fold) after 6 to 12 h. Increased expression of TGF(II mRNA was accompanied by increased TGFO protein production into conditioned medium of AKR-2B cells. Neither TGFI32 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
126
1
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(139 citation statements)
references
References 58 publications
11
126
1
1
Order By: Relevance
“…This sequential regulation of developmental processes by TGF-P isoforms has been suggested by other investigators (Lyons et al, 1990;Fitzpatrick et al, 1990;Gatherer et al, 1990). In addition, studies have found that in some systems TGF-ps do regulate each other (Bascom et al, 1989;Jakowlew et al, 1992;Lehnert and Ackhurst, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…This sequential regulation of developmental processes by TGF-P isoforms has been suggested by other investigators (Lyons et al, 1990;Fitzpatrick et al, 1990;Gatherer et al, 1990). In addition, studies have found that in some systems TGF-ps do regulate each other (Bascom et al, 1989;Jakowlew et al, 1992;Lehnert and Ackhurst, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Mere elevation of TGF-/~ mRNA expression is therefore not automatically an indication that active TGF-/~s are being produced. An example of this is the production of latent TGF-~I by human keratinocytes cultured under serum-free conditions at neutral pH (Bascom et al, 1989 Because the effects of TGF-/~s on basal cell growth appear to be largely reversible, it has been assumed that TGF-~s alone are not sufficient to induce terminal differentiation, a process thought to be irreversible. In support of this notion were early in vitro studies, showing that the biochemical indicators of terminal differentiation were not induced upon treatment of keratinocytes cultured on plastic with TGF-/3s (Kopan et al, 1987;Bascom et al, 1989).…”
Section: Negative Growth Regulatorsmentioning
confidence: 99%
“…An example of this is the production of latent TGF-~I by human keratinocytes cultured under serum-free conditions at neutral pH (Bascom et al, 1989 Because the effects of TGF-/~s on basal cell growth appear to be largely reversible, it has been assumed that TGF-~s alone are not sufficient to induce terminal differentiation, a process thought to be irreversible. In support of this notion were early in vitro studies, showing that the biochemical indicators of terminal differentiation were not induced upon treatment of keratinocytes cultured on plastic with TGF-/3s (Kopan et al, 1987;Bascom et al, 1989). More recent studies with differentiating culture systems have revealed that at greatly elevated levels, TGF-/3s can influence biochemical markers of keratinization, but at these high levels, they inhibit rather than promote, K1, K10, and filaggrin expression (Ma~nsbridge and Hanawalt,..1988;Choi and Fuchs, 1990).…”
Section: Negative Growth Regulatorsmentioning
confidence: 99%
See 2 more Smart Citations